Adobe Premiere Pro CC 2019 release : classroom in a book - Jago, Maxim (San Jose, CA51000360192 : Adobe Press, 2019)
Contains eighteen project-based lessons that cover the basics of Adobe Premium Pro CC, along with tips and techniques to optimize productivity with the program, including such topics as compositing techniques and color correction and grading.
Getting started -- Touring Adobe Premiere Pro CC -- Setting up a project -- Importing media -- Organizing media -- Mastering the essentials of video editing -- Working with clips and markers -- Adding transitions -- Mastering advanced editing techniques -- Putting clips in motion -- Editing and mixing audio -- Sweetening sound -- Adding video effects -- Improving clips with color correction and grading -- Exploring compositing techniques -- Creating graphics -- Exporting frames, clips, and sequences
Keywords: Premiere; Digital video; Datorprogram; Computer software; Computer programs; Digital video; Premiere; Digital video; Digital electronics; Videoredigering; Digitalteknik